2020
DOI: 10.1111/ejn.14656
|View full text |Cite
|
Sign up to set email alerts
|

Assessing neurophysiological changes associated with combined transcranial direct current stimulation and cognitive‐emotional training for treatment‐resistant depression

Abstract: Assessing neurophysiological changes associated with combined transcranial direct current stimulation and cognitive-emotional training for treatment-resistant depression.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 99 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…tDCS is being increasingly used in the treatment of several psychiatric disorders [ 28 ], including depression [ 41 ], obsessive compulsive disorder [ 42 , 43 ], anxiety disorders [ 44 ], substance use disorders [ 45 ], and schizophrenia [ 46 ]. tDCS can be used alone or in combination with other interventions, such as psychotherapy [ 47 ] or cognitive training [ 48 ]. In recent years, tDCS has also been used to treat children and adults with ASD, with no serious adverse events and encouraging results in terms of feasibility, efficacy, and tolerability [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…tDCS is being increasingly used in the treatment of several psychiatric disorders [ 28 ], including depression [ 41 ], obsessive compulsive disorder [ 42 , 43 ], anxiety disorders [ 44 ], substance use disorders [ 45 ], and schizophrenia [ 46 ]. tDCS can be used alone or in combination with other interventions, such as psychotherapy [ 47 ] or cognitive training [ 48 ]. In recent years, tDCS has also been used to treat children and adults with ASD, with no serious adverse events and encouraging results in terms of feasibility, efficacy, and tolerability [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, one tDCS study (Nikolin et al, 2020) also used a 2-mA stimulation current for 40 min. The current was delivered from the left DLPFC to the right shoulder, with patients receiving the therapy three times per week for 6 weeks.…”
Section: Depressive Disordermentioning
confidence: 99%
“…More importantly, few studies have examined the aftereffects of tDCS on these neurophysiological measures immediately after the end of WMT, typically at the end [36,39] or one day after the last training session [4,[32][33][34]. A recent study utilizing resting-state functional magnetic resonance imaging (fMRI) found improved brain network processing efficiency with 3-day of tDCS+WMT one day after training [40].…”
Section: Introductionmentioning
confidence: 99%